The squeaky wheel gets the grease: Violent civil unrest and global social assistance provision - Çemen, Rahmi; Yörük, Erdem (Frontiers in Sociology, 2022)
What are the contemporary determinates of social assistance provision? What is the role of contentious politics? Social assistance literature is dominated by economic and demographic accounts, which under-examine the possibility that governments extend social assistance to contain social unrest. We test factors associated with these “structuralist” and “political” theories on a new panel dataset which includes 54 OECD and emerging market countries between 2002 and 2015. The results indicate social assistance coverage has a significant positive relationship with riots. We explain this outcome as policymakers expanding social assistance as a means of containing violent civil unrest. This effect is more significant in emerging markets, suggesting that the domination of structural explanations is a result of sample bias toward the OECD. Finally, we find that governments consider World Bank social policy recommendations only insofar as there is violent unrest.